Real-world Lyme disease testing results using modified vs standard two-tier test protocols. - Yonghong Li; Zhen Chen; Carmen H Tong; Ky Van; Robert S Jones; Lance A Bare (PLoS ONE, 2025)
The modified two-tier test (MTTT) and standard two-tier test (STTT) protocols are being used for Lyme disease serology testing in the clinic. We aimed to compare the real-world testing results of MTTT, a recently approved protocol, vs STTT, a mainstay protocol over the past decades. To this end, we obtained results of Lyme disease testing performed in a US national reference laboratory in 2022 and 2023 and constructed a matched cohort with 66,708 individuals tested using MTTT and 66,708 individuals tested using STTT. We found that, compared with STTT, MTTT identified more test positives in adults aged 18 and older and similar number of test positives in the children and adolescents. The odds ratio (95% confidence interval) of testing positive using MTTT vs STTT was 1.88 (1.79-1.98) in adults and 1.09 (0.97-1.23) in non-adults. In addition, more patients tested positive for immunoglobulin M antibody alone or positive for both immunoglobulin M and immunoglobulin G antibodies using MTTT than STTT.